Hubungan Anemia Pada Ibu Hamil Terhadap Kejadian BBLR di RSIA Sitti Khadijah 1 Makassar - Burhan, KHartina; Dahliah, Dahliah; Karsa, Nevi Sulvita (Wal'afiat Hospital Journal, 2021)
In 2011, there were 32.4 million pregnant women aged 15-49 years in the world experiencing anemia. Data (WHO 2011) shows that around (30%) pregnant women in Indonesia experience anemia. This figure is higher compared to some other countries in Southeast Asia such as Malaysia (27%), Singapore (28%), and Vietnam (23%). This study aims to determine the relationship of anemia in pregnant women with the incidence of low birth weight babies (LBW) in the Mother and Child Hospital Sitti Khadijah 1 Makassar in 2018. Research conducted is descriptive analytic using cross sectional method in which a study, variables including risk factors and variables including effects are observed at once at the same time. Based on data from 70 pregnant women who have anemia, there are 66 pregnant women classified as mild anemia (94.3%) and 4 pregnant women with moderate anemia category (5.7%). Of the 23 pregnant women who gave birth to LBW babies were categorized into mild anemia as many as 22 (31.4%) and moderate anemia as much as 1 (1.42%). Based on the chi-square statistical test results obtained p value more than 0.05 (p = 0.601) which means there is no significant relationship between anemia in pregnant women with the incidence of low birth weight in the Mother and Child Hospital Sitti Khadijah 1 Makassar in 2018.